A viewpoint on ecological and evolutionary study of plant thermal performance curves in a warming world. Issue 3 (13th April 2022) - Wooliver, Rachel; Vtipilthorpe, Emma E; Wiegmann, Amelia M; Sheth, Seema N
Abstract: We can understand the ecology and evolution of plant thermal niches through thermal performance curves (TPCs), which are unimodal, continuous reaction norms of performance across a temperature gradient. Though there are numerous plant TPC studies, plants remain under-represented in syntheses of TPCs. Further, few studies quantify plant TPCs from fitness-based measurements (i.e. growth, survival and reproduction at the individual level and above), limiting our ability to draw conclusions from the existing literature about plant thermal adaptation. We describe recent plant studies that use a fitness-based TPC approach to test fundamental ecological and evolutionary hypotheses, some of which have uncovered key drivers of climate change responses. Then, we outline three conceptual questions in ecology and evolutionary biology for future plant TPC studies: (i) Do populations and species harbour genetic variation for TPCs? (ii) Do plant TPCs exhibit plastic responses to abiotic and biotic factors? (iii) Do fitness-based TPCs scale up to population-level thermal niches? Moving forward, plant ecologists and evolutionary biologists can capitalize on TPCs to understand how plasticity and adaptation will influence plant responses to climate change. Abstract : Variation in plant performance across temperatures are illustrated with a thermal performance curve (TPC), where performance peaks at a benign temperature and decreases to zero as temperature becomes cooler or warmer. Thermal performance curves have been useful for understanding evolution and plasticity, especially in response to climate change. However, most plant TPCs in the literature are based on physiological traits of single leaves, rather than individual fitness which would more directly approximate how populations might respond to changes in temperature. We describe what has been done and necessary next steps that utilize TPCs to determine how plants will respond to climate change.